Water security and spring conservation in the Himalaya - Kumar, Manish; Rathod, R.; Mukherji, Aditi (Springer, 2023)
Springs are the most important source of water for the people in the mid-hills of the Himalaya. Emerging evidence shows that they are increasingly drying up, causing numerous hardships for people, with those impacts being felt more acutely by women and members of vulnerable communities like lower castes (Dalits). Climate change, land-use and land cover changes, including haphazard infrastructure (hydropower, road construction), and other socio-economic changes such as urbanization and tourism are the leading causes of the drying up of springs. In the region in general, and India in particular, the last decade and a half have seen increased initiatives for spring revival. In this chapter, we document the genesis of some of these spring revival initiatives in India and note how all stakeholders—communities, civil societies and governments have come to support spring revival initiatives. We also note that the scientific community has not yet caught up with the action on the ground, and we still lack rigorous documentation of the short and long-term effectiveness of spring revival initiatives. We recommend integrating scientific knowledge with social analysis on the governance aspects for improving spring recharge, better management and postulating potential responses of natural and human systems against future climate change impacts in the Himalaya.